Development of Instant Coffee for Value Adding of Coffee Products from Ban Borsiliam, Ngao District, Lampang Province - Wirunthanakrit*, Weerapong; Vittayaporn, Varaporn (Journal of Food Health and Bioenvironmental Science, 2018)
This research aimed to develop an instant coffee using the coffee beans from Ban Borsiliam, Ngao District, Lampang Province, as to increase the product’s value. Surveys for fundamental data and the demand to develop a coffee product of Ban Borsiliam, Ngao District, Lampang Province were conducted, and it has been found that the locally cultivated coffee was Arabica, which yields approximately 5,000 Kilograms of gross product per annum. The commercial products of the community included parchment coffee beans, honey-process coffee beans, and roasted coffee beans. The study on the condition with spray drying found that the optimal inlet temperature of the spray dryer for developing the instant coffee was at 160°C. The wall material used to encapsulate the coffee extract was 10% maltodextrin. The developed formula of the 3-in-1 instant coffee mix comprises 15.9% instant coffee, 36.3% sugar, 47.6% non-dairy creamer, and 0.2% flavor. The consumer acceptance test showed that the mean liking score toward the 3-in-1 instant coffee was at the moderately like to very like level (7.4±0.8), with 92%of consumers accepting the developed 3-in-1 instant coffee, and 88% of consumers that would purchase the product if available in the market. The results regarding the satisfaction toward the technology transfer of this study found that the participants scored between very satisfied and most satisfied.